High contrast race and gender in contemporary Hollywood films - Willis, Sharon (Durham, N.C. : Duke University Press, 1998)
In High Contrast, Sharon Willis examines the dynamic relationships between racial and sexual difference in Hollywood film from the 1980s and 1990s.
Seizing on the way these differences are accentuated, sensationalized, and eroticized on the screen - most often with little apparent regard for the political context in which they operate - Willis restores that context through close readings of a range of movies from cinematic blockbusters to the work of the new auteurs, Spike Lee, David Lynch, and Quentin Tarantino.
Pt. I. Battles of the Sexes. 1. Mutilated Masculinities and Their Prostheses: Die Hards and Lethal Weapons. 2. Insides Out: Public and Private Exchanges from Fatal Attraction to Basic Instinct. 3. Combative Femininity: Thelma and Louise and Terminator 2 -- Pt. II. Ethnographies of the "White" Gaze. 4. Do the Wrong Thing: David Lynch's Perverse Style. 5. Tell the Right Story: Spike Lee and the Politics of Representative Style. 6. Borrowed "Style": Quentin Tarantino's Figures of Masculinity.
Includes index.
Keywords: African Americans in motion pictures; Sex role in motion pictures